CLC (Community Learning Center) Think Indonesia School as the Learning Internship Practices for Department of Nonformal Education UNESA Students - Rosyanafi, Rofik Jalal (Lembaran Ilmu Kependidikan, 2023)
Internship is one of the compulsory subjects for students. This internship program is a bridge to implement the theory that has been learned by students while conducting lectures with actual professional conditions in their scientific fields, including students majoring in Nonformal Education semester 7 who carry out their internship activities at CLC (Community Learning Center) Think Indonesia School. This type of research is descriptive research conducted using a qualitative approach, to analyze apprenticeships as learning practices carried out by students majoring in Nonformal Education. The data sources used in this study are primary and secondary sources collected through data collection techniques in the form of observation, interviews, and documentation, with the data analysis technique applied is the Miles and Huberman model. The results obtained in this study are that in carrying out internship activities, students participate in socializing the acceptance of new students (PPDB), preparing annual programs, compiling SOP and making habituations in the learning process, becoming study tutors, making lesson plans, and evaluating learning in management. PKBM institutions to provide an overview, abilities, skills in managing educational institutions and skilled in conducting learning.